The Essence of the Fundamental Rights to Privacy and Data Protection: Finding the Way Through the Maze of the CJEU's Constitutional Reasoning. Issue 6 (September 2019) - Brkan, Maja
Abstract: In the constitutional shaping of the concept of essence of fundamental rights, the case law of the Court of Justice of the EU ("CJEU" or "the Court") in the field of privacy and data protection plays a crucial role. The Court's interpretation of this notion had a considerable impact not only jon perception of the essence in other fields of law, but also on the constitutional doctrine more generally. This Article focuses on specificities of the notion of essence of fundamental rights to privacy and the protection of personal data from Articles 7 and 8 of the Charter of Fundamental Rights of the EU. After a general analysis, situating this notion into the framework of multi-level protection of fundamental rights in Europe, the Article addresses further interpretative challenges relating to the essence in the Court's case law. At the core of the analysis are the Schrems and Digital Rights Ireland cases, where the CJEU developed, for the first time, the modalities of the breach of essence of fundamental rights to privacy and data protection and laid down constitutional foundations for interpretation of this notion. Further jurisprudence, including the Tele2 Sverige and Opinion 1/15 cases, is analyzed as an example of fine-tuning of the CJEU's approach towards the normative understanding of this concept. Against this backdrop, the Article elaborates on the importance of insights in the fields of privacy and data protection for the general constitutional understanding of the concept of essence and proposes a generalized method for determination of infringement of essence in fundamental rights jurisprudence.